Estudio de factibilidad para la creación de una incubadora de microempresas GAD municipal cantón El Empalme, año 2015 - Vega Adriances, José Roberto (2016)
This research was based on a study of feasibility for the creation of a feasibility study for the creation of an incubator of micro GADM Canton Junction, 2015. Currently the canton of El Empalme has a population of 81.015 inhabitants which it makes it attractive for establishing a business. To find the viability of the feasibility study was used to conduct four studies which are: market research, technical study, economic study and financial study, which will give them the necessary information for decision making. Manifests serving as the first objective of the research on developing a market study showed that this acceptance is high that the population by creating a micro-incubator due to unmet demand for this type of business. EMPRODUCTIVO microenterprise incubator is located on the corner of the junction between Av. Quevedo and May 2, the store will feature a physical space of 200 square meters. Through economic study - financial result was obtained as follows; they go from $ 46.001.22 dollars: IRR of 32%; Benefit - cost $ 1.52 cents, indicators have proven viable for the setting up of micro incubator EMPRODUCTIVO keyword Feasibility study Market study Technical study Economic study Financial study Viability Cost effectiveness GO TIR Breakeven.